Influence of Service Quality and Sales in Textile Companies, Trujillo 2023 - Jara Gonzales, Jhonar Denis; Méndez-Gutiérrez, Leidy Lucia; Flores-Dianderas, Katherine Roxana (LACCEI, 2024)
The study examines the factors influencing textile companies, which play a crucial role in society. The relational marketing theory was considered for this purpose. The objective was to demonstrate the influence of service quality on sales in textile companies in Trujillo. A descriptive correlational causal approach was adopted, supported by a non-experimental cross-sectional design with a quantitative focus. The sample consisted of 46 customers surveyed during their visits to textile companies. The results confirmed the acceptance of the alternative hypothesis, with a Spearman coefficient (Rho) of 0.637, indicating a moderate positive correlation. These findings highlight the need to prioritize service quality in the textile sector and provide a robust basis for strategic decision-making and the implementation of improvements in business management. It was revealed that offering quality service directly influences sales growth. Therefore, overall, it is important to consider this for national growth.